A cellulose-based refractory triboelectric material and a preparation method thereof
By grafting hydroxyapatite on the surface of nanocellulose, the problems of flammability and high temperature resistance of traditional cellulose-based friction electric materials are solved, and the preparation of cellulose-based refractory friction electric materials is realized, with good refractory and flame retardant properties and high output electrical properties.
Patent Information
- Application Number
- CN202310058994.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-01-17
- Publication Date
- 2025-04-08
- Estimated Expiration
- 2043-01-17
AI Technical Summary
Traditional cellulose-based triboelectric materials are flammable and not resistant to high temperatures, making it difficult to maintain effective performance under high temperature and flammable ambient conditions.
By grafting hydroxyapatite on the surface of nanocellulose, a cellulose-based refractory triboelectric material is formed, and the chemical bonds of hydroxyapatite are used to bind to the nanocellulose surface to enhance the refractory and flame retardant properties of the material.
The refractory and flame retardant performance of cellulose-based materials has been improved, and the problems of flammability and unresistance to high temperatures are overcome, while maintaining good output electrical performance in high temperature environments.
Smart Images

Figure HDA0004060944110000011 
Figure HDA0004060944110000012 
Figure HDA0004060944110000013
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of functional materials, and in particular relates to a cellulose-based fire-resistant triboelectric material and a preparation method thereof. Background Art
[0002] Hydroxyapatite (HAP) is a typical inorganic calcium phosphate material and is a natural mineralization of calcium apatite (Ca5(PO4)3(OH)). Hydroxyl groups can be replaced by fluoride, chloride and carbonate ions to form fluoride-based apatite or chloride-based apatite, where calcium ions can be replaced by a variety of metal ions through ion exchange reactions to form M apatite corresponding to the metal ions (M represents the metal ion that replaces the calcium ion). Hydroxyapatite has the advantages of excellent biocompatibility, ion exchange and adsorption capacity, thermal stability, and fire resistance.
[0003] Cellulose is the most widely distributed and abundant polysaccharide in nature, accounting for more than 50% of the carbon content in the plant kingdom. As one of the most abundant natural polymers in nature, cellulose has the advantages of wide sources, low cost, and sustainability. Thanks to the abundant hydroxyl groups on the molecular surface, it provides sufficient reaction sites for its chemical reaction customization. Therefore, cellulose is also considered to be a future-oriented, advanced triboelectric material.
[0004] However, traditional cellulose-based triboelectric materials still face performance defects such as flammability and high temperature resistance. Therefore, the development of fire-resistant and flame-retardant cellulose-based triboelectric materials has become one of the research hotspots in the field of triboelectric nanogenerators (TENGs).
[0005] Therefore, the present invention realizes the preparation of fire-resistant and flame-retardant cellulose-based triboelectric materials by grafting hydroxyapatite on the surface of nanocellulose, providing a new idea for the construction and application of cellulose-based functional materials under high temperature and flammable environment conditions. Summary of the invention
[0006] In view of the above problems, the present invention provides a method for preparing a cellulose-based fire-resistant triboelectric material. By grafting hydroxyapatite on the surface of nanocellulose, the prepared cellulose-based fire-resistant triboelectric material has excellent fire-resistant and flame-retardant properties.
[0007] The present invention is achieved through the following technical solutions:
[0008] A method for preparing a cellulose-based fire-resistant triboelectric material comprises the following steps:
[0009] (1) Preparation of hydroxyapatite: Methanol, deionized water and oleic acid are taken and stirred at room temperature to mix evenly, and then sodium hydroxide solution, calcium chloride solution and sodium dihydrogen phosphate dihydrate solution are added and stirred, and the obtained mixed solution is transferred to a reactor for hydrothermal reaction. After the reaction is completed, the mixture is cooled to room temperature, and the product is taken out, washed and freeze-dried to obtain hydroxyapatite;
[0010] (2) Grafting hydroxyapatite on the surface of nanocellulose: Take nanocellulose pulp and add it to N,N-dimethylformamide solution, stir, ultrasonicate and centrifuge. At the same time, disperse hydroxyapatite in the solution and stir. Then add isophorone diisocyanate and dibutyltin dilaurate. The obtained mixed solution is esterified at high temperature. The solution after the reaction is centrifuged. The obtained precipitate is washed, centrifuged and filtered to obtain a cellulose-based refractory triboelectric material.
[0011] Furthermore, in step (2), the mass ratio of the nanocellulose pulp to hydroxyapatite is 10:0.5-2, and the mass fraction of the nanocellulose pulp is 5-6wt%.
[0012] Furthermore, in step (2), the mass ratio of hydroxyapatite to dibutyltin dilaurate is 1 g: (1-2) mL.
[0013] Furthermore, in step (2), the volume ratio of the N,N-dimethylformamide solution, isophorone diisocyanate and dibutyltin dilaurate is 45-50:45-50:1.
[0014] Furthermore, in step (2), the esterification reaction is carried out at 100-120° C. for 2-3 hours under the condition of introducing argon and excluding air.
[0015] Furthermore, in step (1), the volume ratio of the sodium hydroxide solution, the calcium chloride solution and the sodium dihydrogen phosphate dihydrate solution is 1:0.5 to 1:1 to 1.5.
[0016] Furthermore, in step (1), the concentration of the sodium hydroxide solution is 1.5 to 2 mol / L, the concentration of the calcium chloride solution is 0.2 to 0.4 mol / L, and the concentration of the sodium dihydrogen phosphate dihydrate solution is 0.2 to 0.5 mol / L.
[0017] Furthermore, in step (1), the volume ratio of the methanol, deionized water and oleic acid is 1:2-2.5:1.5-2, and the volume ratio of the methanol and sodium hydroxide solution is 0.3-0.5:1.
[0018] Furthermore, in step (1), the hydrothermal reaction is carried out at 160-200° C. for 22-25 hours.
[0019] Furthermore, in step (1), the freeze-drying time is 55 to 60 hours.
[0020] A cellulose-based refractory triboelectric material is prepared by the above-mentioned method for preparing a cellulose-based refractory triboelectric material.
[0021] The reaction principle of the present invention is: Figure 1 As can be seen from the schematic diagram of the esterification reaction, in the present invention, N,N-dimethylformamide solution is used as a reaction solvent, and dibutyltin dilaurate is used as a catalyst to catalyze the reaction between isophorone diisocyanate and hydroxyl groups. The two -NCO groups on isophorone diisocyanate react with the -OH on nanocellulose and the -OH on hydroxyapatite to generate -NCOOH groups, and the hydroxyapatite is grafted to the surface of the nanocellulose by means of chemical bonds.
[0022] Compared with the prior art, the advantages and beneficial effects of the present invention are:
[0023] 1. The present invention obtains a cellulose-based fire-resistant triboelectric material by grafting hydroxyapatite on the surface of nanocellulose. Hydroxyapatite is grafted to the surface of nanocellulose due to the effect of chemical bonds, forming a coating effect, which has a good protective effect on the nanocellulose, so that the prepared material has good fire-resistant and flame-retardant properties, overcoming the shortcomings of cellulose-based materials that are flammable and not resistant to high temperatures.
[0024] 2. In the preparation method of the present invention, N, N-dimethylformamide solution is used as a reaction solvent, dibutyltin dilaurate is used as a catalyst, and under the conditions of passing argon gas, excluding air and high temperature, isophorone diisocyanate undergoes an esterification reaction with nanocellulose and hydroxyapatite, and hydroxyapatite is successfully grafted onto the surface of nanocellulose. The preparation method of the material of the present invention is simple to operate, easy to implement, and has good practical application value.
[0025] 3. The cellulose-based fire-resistant triboelectric material of the present invention has good fire resistance, and still maintains a good morphology after burning for 1 minute, and has high output electrical performance, with a current of up to 6.18μA, a surface charge density of up to 41nC, and a voltage of up to 102V. The preparation of the cellulose-based fire-resistant triboelectric material of the present invention provides a new idea for the construction and application of cellulose-based functional materials under high temperature and flammable environment conditions. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] Figure 1 Schematic diagram of the esterification reaction in Example 2.
[0027] Figure 2 This is a SEM image of the cellulose-based refractory triboelectric material of Example 2 at a magnification of 1000.
[0028] Figure 3 This is a SEM image of the cellulose-based refractory triboelectric material of Example 2 at a magnification of 10,000.
[0029] Figure 4 This is the FTIR graph of the cellulose-based refractory triboelectric material of Example 2.
[0030] Figure 5 Graphs showing the current flow of the cellulose-based fire-resistant triboelectric materials of Examples 1-4.
[0031] Figure 6 Surface charge density diagram of the cellulose-based refractory triboelectric material of Examples 1-4.
[0032] Figure 7 1 is a voltage diagram of the cellulose-based fire-resistant triboelectric material of Examples 1-4.
[0033] Figure 8 This is a graph showing the fire resistance performance of the cellulose-based fire-resistant triboelectric material of Example 2 when burned under the flame of an alcohol lamp for 1 minute. DETAILED DESCRIPTION
[0034] The present invention is further described in detail below by way of examples. These examples are only used to illustrate the present invention and do not limit the protection scope of the present invention.
[0035] Example 1
[0036] Preparation of cellulose-based refractory triboelectric materials:
[0037] (1) Preparation of hydroxyapatite: 10 mL of methanol, 22 mL of deionized water and 18 mL of oleic acid were taken and stirred at room temperature to mix evenly, and then 27 mL of 1.5 mol / L sodium hydroxide solution, 25 mL of 0.3 mol / L calcium chloride solution and 32 mL of 0.4 mol / L sodium dihydrogen phosphate dihydrate solution were added and stirred, and the resulting mixed solution was transferred to a reactor for hydrothermal reaction at 160° C. for 25 h. After the reaction was completed, the mixture was cooled to room temperature, the product was taken out, washed with ethanol, and freeze-dried for 58 h to obtain hydroxyapatite;
[0038] (2) Grafting hydroxyapatite on the surface of nanocellulose: Take 10g of 5wt% nanocellulose pulp and add it to 25mL N,N-dimethylformamide solution, stir, ultrasonicate for 10min, centrifuge for 10min, and at the same time disperse 0.5g of hydroxyapatite in the solution, stir, then add 25mL of isophorone diisocyanate and 0.5mL of dibutyltin dilaurate, and subject the obtained mixed solution to esterification reaction at high temperature. Under the condition of passing argon and excluding air, react at 100°C for 2h, centrifuge the solution after the reaction, and wash the obtained precipitate in N,N-dimethylformamide solution and anhydrous ethanol, centrifuge, and filter to obtain a cellulose-based refractory triboelectric material.
[0039] Example 2
[0040] Preparation of cellulose-based refractory triboelectric materials:
[0041] (1) Preparation of hydroxyapatite: 12 mL of methanol, 27 mL of deionized water and 21 mL of oleic acid were taken and stirred at room temperature to mix evenly, and then 30 mL of 1.75 mol / L sodium hydroxide solution, 24 mL of 0.25 mol / L calcium chloride solution and 36 mL of 0.33 mol / L sodium dihydrogen phosphate dihydrate solution were added and stirred, and the resulting mixed solution was transferred to a reactor for hydrothermal reaction at 180° C. for 24 h. After the reaction was completed, the mixture was cooled to room temperature, the product was taken out, washed with ethanol, and freeze-dried for 60 h to obtain hydroxyapatite;
[0042] (2) Grafting hydroxyapatite on the surface of nanocellulose: Take 10g of 5wt% nanocellulose pulp and add it to 50mL N,N-dimethylformamide solution, stir, ultrasonicate for 10min, centrifuge for 10min, and at the same time disperse 1g of hydroxyapatite in the solution, stir, then add 50mL of isophorone diisocyanate and 1mL of dibutyltin dilaurate, and esterify the obtained mixed solution at high temperature. Under the condition of passing argon and excluding air, react at 110°C for 3h, centrifuge the solution after the reaction, and wash the obtained precipitate in N,N-dimethylformamide solution and anhydrous ethanol, centrifuge, and filter to obtain cellulose-based refractory triboelectric material (abbreviated as CNF@HAP).
[0043] Example 3
[0044] Preparation of cellulose-based refractory triboelectric materials:
[0045] (1) Preparation of hydroxyapatite: 15 mL of methanol, 35 mL of deionized water and 25 mL of oleic acid were taken and stirred at room temperature to mix evenly, and then 35 mL of 2 mol / L sodium hydroxide solution, 30 mL of 0.4 mol / L calcium chloride solution and 40 mL of 0.5 mol / L sodium dihydrogen phosphate dihydrate solution were added and stirred. The resulting mixed solution was transferred to a reactor for hydrothermal reaction at 200° C. for 23 h. After the reaction was completed, the mixture was cooled to room temperature, the product was taken out, washed with ethanol, and freeze-dried for 60 h to obtain hydroxyapatite.
[0046] (2) Grafting hydroxyapatite on the surface of nanocellulose: Take 10g of 5wt% nanocellulose pulp and add it to 75mL N,N-dimethylformamide solution, stir, ultrasonicate for 15min, centrifuge for 15min, and at the same time disperse 1.5g of hydroxyapatite in the solution, stir, then add 75mL of isophorone diisocyanate and 1.5mL of dibutyltin dilaurate, and subject the obtained mixed solution to esterification reaction at high temperature. Under the condition of passing argon and excluding air, react at 120℃ for 3h, centrifuge the solution after the reaction, and wash the obtained precipitate in N,N-dimethylformamide solution and anhydrous ethanol, centrifuge and filter to obtain a cellulose-based refractory triboelectric material.
[0047] Example 4
[0048] Preparation of cellulose-based refractory triboelectric materials:
[0049] (1) Preparation of hydroxyapatite: 14 mL of methanol, 30 mL of deionized water and 28 mL of oleic acid were taken and stirred at room temperature to mix evenly, and then 32 mL of 1.8 mol / L sodium hydroxide solution, 28 mL of 0.2 mol / L calcium chloride solution and 35 mL of 0.2 mol / L sodium dihydrogen phosphate dihydrate solution were added and stirred, and the resulting mixed solution was transferred to a reactor for hydrothermal reaction at 160° C. for 25 h. After the reaction was completed, the mixture was cooled to room temperature, the product was taken out, washed with ethanol, and freeze-dried for 55 h to obtain hydroxyapatite;
[0050] (2) Grafting hydroxyapatite on the surface of nanocellulose: Take 10g of 5wt% nanocellulose pulp and add it to 100mL N,N-dimethylformamide solution, stir, ultrasonicate for 10min, and centrifuge for 10min. At the same time, disperse 2g of hydroxyapatite in the solution and stir. Then add 90mL of isophorone diisocyanate and 2mL of dibutyltin dilaurate. The obtained mixed solution is subjected to esterification reaction at high temperature. Under the condition of passing argon and excluding air, the reaction is carried out at 120°C for 3h. The solution after the reaction is centrifuged, and the obtained precipitate is washed in N,N-dimethylformamide solution and anhydrous ethanol, centrifuged, and filtered to obtain a cellulose-based refractory triboelectric material.
[0051] Material morphology characterization and analysis
[0052] (I) SEM analysis
[0053] The cellulose-based fire-resistant triboelectric material of Example 2 was characterized and analyzed using a scanning electron microscope (SEM). Figure 2 and Figure 3 As shown, Figure 2 This is a SEM image of the cellulose-based fire-resistant triboelectric material of Example 2 at 1000 times magnification, Figure 3 This is a SEM image of the cellulose-based refractory triboelectric material of Example 2 at a magnification of 10,000.
[0054] Depend on Figure 2 and Figure 3 It can be seen that hydroxyapatite is evenly dispersed on the surface of the CH membrane, and the hydroxyapatite grafted on the surface of nanocellulose protects the nanocellulose well.
[0055] (ii) FTIR analysis
[0056] The cellulose-based fire-resistant triboelectric material of Example 2 was characterized and analyzed by Fourier transform infrared spectroscopy (FTIR). Figure 4 As shown, Figure 4 This is the FTIR graph of the cellulose-based refractory triboelectric material of Example 2, wherein HAP represents hydroxyapatite, CNF represents nanocellulose, and CNF@HAP represents a cellulose-based refractory triboelectric material.
[0057] Depend on Figure 4 It can be seen that the cellulose-based refractory triboelectric material prepared in Example 2 has a -1 A new ester peak appears at the bottom, indicating that hydroxyapatite is successfully grafted on the surface of nanocellulose.
[0058] Material performance test analysis
[0059] (I) Electrical performance test
[0060] The cellulose-based fire-resistant triboelectric material of Examples 1-4 was cut into 2 cm × 2 cm squares and pasted on an acrylic plate with conductive glue as the positive electrode material. A fluorinated ethylene propylene copolymer (FEP) film of the same size was cut as the negative electrode material and pasted on an acrylic plate with conductive glue. The positive and negative plates were respectively mounted on the TENG electrical test bench to form a vertical-contact separation mode TENG. The test was carried out at a frequency of 1 Hz. The test results are shown in FIG. Figure 5 , Figure 6 and Figure 7 As shown, Figure 5 is the current diagram of the cellulose-based refractory triboelectric material of Examples 1-4, Figure 6 is the surface charge density diagram of the cellulose-based refractory triboelectric material of Examples 1-4, Figure 7 1 is a voltage diagram of the cellulose-based fire-resistant triboelectric material of Examples 1-4. Figure 5-7 , CH-11, CH-12, CH-13, and CH-14 represent that the mass ratios of nanocellulose (CNF) to hydroxyapatite (HAP) in Examples 1, 2, 3, and 4 are 1:1, 1:2, 1:3, and 1:4, respectively.
[0061] Depend on Figure 5-7 It can be seen that the current, surface charge density and voltage of the cellulose-based refractory triboelectric materials of Examples 1, 3 and 4 are lower than those of the material of Example 2. When the mass ratio of nanocellulose to hydroxyapatite in Example 2 is 1:2, the current, surface charge density and voltage of the prepared cellulose-based refractory triboelectric material are the highest, which are 6.18 μA, 41 nC and 102 V, respectively.
[0062] The change in electrical properties of the materials in Examples 1-4 is due to the change in bond energy between nanocellulose and hydroxyapatite in different mass ratios. Since nanocellulose contains a large number of hydroxyl groups, the structure of the nanocellulose itself easily produces a large number of hydrogen bonds, which affects the mobility of polarized groups. Since the grafted hydroxyapatite forms new ester bonds, the hydrogen bond content is reduced and the migration of polarized groups is increased, thereby enhancing the dielectric constant of the composite material. However, due to the limited grafting sites, the amount of grafted hydroxyapatite is limited, and the excess hydroxyapatite causes the presence of ungrafted hydroxyapatite monomers in the mixed system, which causes the hydrogen bonds of the composite material to increase again, thereby reducing the mobility of polarized groups in nanocellulose, reducing the dielectric constant, and causing a decrease in electrical properties.
[0063] (II) Fire retardant properties
[0064] The cellulose-based fire-resistant triboelectric material of Example 2 was placed under the flame of an alcohol lamp and burned for 1 min. Figure 8 As shown, Figure 8 This is a graph showing the fire resistance performance of the cellulose-based fire-resistant triboelectric material of Example 2 when burned under the flame of an alcohol lamp for 1 minute.
[0065] from Figure 8 It can be seen that the cellulose-based fire-resistant triboelectric material of Example 2 has good fire resistance. The reason is that hydroxyapatite is grafted onto the surface of nanocellulose due to the effect of chemical bonds, forming a coating effect and protecting the nanocellulose.
Claims
1. A method for preparing a cellulose-based refractory triboelectric material, characterized in that: The following steps are involved: (1) Preparation of hydroxyapatite: Methanol, water and oleic acid are taken and stirred at room temperature to mix evenly, and then sodium hydroxide solution, calcium chloride solution and sodium dihydrogen phosphate dihydrate solution are added and stirred, and the resulting mixed solution is transferred to a reactor for hydrothermal reaction. After the reaction is completed, the mixture is cooled to room temperature, and the product is taken out, washed and freeze-dried to obtain hydroxyapatite; (2) Grafting hydroxyapatite on the surface of nanocellulose: Take nanocellulose pulp and add it to N,N-dimethylformamide solution, stir, ultrasonicate and centrifuge. At the same time, disperse hydroxyapatite in the solution and stir. Then add isophorone diisocyanate and dibutyltin dilaurate. After esterification reaction, centrifuge the reaction solution, wash, centrifuge and filter the obtained precipitate to obtain a cellulose-based refractory triboelectric material.
2. The method for preparing a cellulose-based refractory triboelectric material according to claim 1, characterized in that: In step (2), the mass ratio of the nanocellulose pulp to hydroxyapatite is 10:0.5-2, and the mass fraction of the nanocellulose pulp is 5-6 wt%.
3. The method for preparing a cellulose-based refractory triboelectric material according to claim 2, characterized in that: In step (2), the mass volume ratio of the hydroxyapatite to dibutyltin dilaurate is 1 g: (1-2) mL.
4. The method for preparing a cellulose-based refractory triboelectric material according to claim 3, characterized in that: In step (2), the volume ratio of the N,N-dimethylformamide solution, isophorone diisocyanate and dibutyltin dilaurate is 45-50:45-50:
1.
5. The method for preparing a cellulose-based refractory triboelectric material according to claim 1, characterized in that: In step (2), the esterification reaction is carried out at 100-120° C. for 2-3 h under the condition of passing argon gas and excluding air.
6. The method for preparing a cellulose-based refractory triboelectric material according to claim 1, characterized in that: In step (1), the volume ratio of the sodium hydroxide solution, the calcium chloride solution and the sodium dihydrogen phosphate dihydrate solution is 1:0.5 to 1:1 to 1.
5.
7. The method for preparing a cellulose-based refractory triboelectric material according to claim 6, characterized in that: In step (1), the concentration of the sodium hydroxide solution is 1.5-2 mol / L, the concentration of the calcium chloride solution is 0.2-0.4 mol / L, and the concentration of the sodium dihydrogen phosphate dihydrate solution is 0.2-0.5 mol / L.
8. The method for preparing a cellulose-based refractory triboelectric material according to claim 6, characterized in that: In step (1), the volume ratio of methanol, water and oleic acid is 1:2-2.5:1.5-2, and the volume ratio of methanol and sodium hydroxide solution is 0.3-0.5:
1.
9. The method for preparing a cellulose-based refractory triboelectric material according to claim 1, characterized in that: In step (1), the hydrothermal reaction is carried out at 160-200° C. for 22-25 h.
10. A cellulose-based refractory triboelectric material obtained by the method for preparing a cellulose-based refractory triboelectric material according to any one of claims 1 to 9.
Citation Information
Patent Citations
High-performance polyurethane as well as preparation method and application thereof
CN107686549A
Preparation method of nanocellulose / hydroxyapatite nanospheres
CN111690155A